Microwave-Assisted Synthesis of Benzo[4,5]imidazo[1,2-a]pyrimidines from β-Bromo-α,β-unsaturated Aldehydes and 2-Aminobenzimidazoles - Ho, Son Long; Dao, Pham Duy Quang; Cho, Chan Sik (Synlett, 2017)
β-Bromo-α,β-unsaturated aldehydes react with 2-aminobenzimidazoles by microwave irradiation in the presence of a base and magnesium sulfate to give the corresponding benzo[4,5]imidazo[1,2-a]pyrimidines in moderate to good yields.
Keywords: cyclization; heterocycles; aldehydes; fused-ring systems; coupling